Factors Affecting on Environmental Strategy in SMEs manufacturing Firms of a developing country: Mediating role of Green Employee Behavior [version 2; peer review: 2 approved, 1 approved with reservations] - Md Billal Hossain; Sarmad Ejaz; Faisal Ejaz; Jorge Alberto Esponda Perez; Ummi Naiemah Saraih; Ikramuddin Junejo (F1000Research)
Background Sustainability in small and medium-sized enterprises (SMEs) which engage heavily in manufacturing provides them with an essential platform for implementing environmental strategy, which is aimed at reducing environmental damage and promoting environmental protection. This study aims to examine the impact of the reduction in resource use, the greening of processes and products on environmental strategy and the mediating role of green employee behaviour. Methods Primary data gathered with the help of questionnaires from employees of SMEs manufacturing in developing countries, Pakistan. The research gathered data from 211 participants by applying a pre-tested instrumental questionnaire and structural equation modelling (SEM) SmartPLS version 3 was used for data analysis. Results The results confirmed all direct effects, including a reduction in resource use, the greening of processes and products and green employee behaviour of environmental strategies in small and medium manufacturing firms. Also, confirmed partial mediation effect of green employee behavior between greening of processes and products and environmental strategy. Conclusion The current study clearly showed the need for programs and infrastructures that support resource reduction and greening businesses in SMEs. Companies’ implementation of green processes and technologies allows SMEs to take an environmentally responsible stand and become part of the movement toward sustainability. The research stresses the importance of green employee conduct as a mediator, the central point being the individual employee being engaged and aware of the subject and willing to participate in environmentally friendly practices. Therefore, small and medium enterprises should enlighten their staff to practice green behaviour, give them what they need and empower them to be change drivers that will trigger sustainability throughout the organisations.